The Role of the Paratenon in Achilles Tendon Healing: A Study in Rats. Issue 5 (April 2018) - Müller, Sebastian A.; Evans, Christopher H.; Heisterbach, Patricia E.; Majewski, Martin
Background: The role of the paratenon in tendon healing is unknown. The present study compares healing in the presence or absence of the paratenon in an Achilles tendon defect model in rats. Hypothesis: Resection of the paratenon impairs tendon healing. Study Design: Controlled laboratory study. Methods: Sixty skeletally mature Sprague Dawley rats were randomly assigned to either a resected paratenon (RP) group or an intact paratenon (IP) group. In all animals, a 4-mm portion of the Achilles tendon was resected in the midsubstance. In the RP group, the paratenon was resected completely. In the IP group, the paratenon was opened longitudinally and closed again after the tendon defect had been created. One, 2, and 4 weeks after surgery, 7 animals per group were tested biomechanically and 3 animals per group examined histologically. Results: The recovery of mechanical strength was much more rapid in IP tendons. Tear resistance was significantly increased for IP tendons (41.3 ± 8.8 N and 47.3 ± 14.1 N, respectively) compared with RP tendons (19.3 ± 9.1 N and 33.2 ± 6.4 N, respectively) after 1 and 2 weeks. The cross-sectional area was larger in the IP group after 1 and 2 weeks (8.2 ± 2.3 mm 2 and 11.3 ± 3.1 mm 2 vs 5.0 ± 2.4 mm 2 and 5.9 ± 2.0 mm 2, respectively) compared with the RP group. Tendon stiffness was greater in the IP group after 1 week (10.4 ± 1.9 N/mm vs 4.5 ± 1.6 N/mm, respectively) compared with the RP group. In comparison, normal contralateral tendons had a maximal tear resistance of 56.6 ± 7.2 N, a cross-sectional area of 3.6 ± 0.7 mm 2, and stiffness of 17.3 ± 3.8 N/mm. Hematoxylin and eosin staining revealed slightly delayed healing of RP tendons. Early collagen formation was seen in the IP group already after 1 week, whereas in the RP group, this only occurred after 2 weeks. After 4 weeks, the IP tendons showed more collagen crimp formation than the RP tendons. Conclusion: An intact paratenon promotes healing of the Achilles tendon. Clinical Relevance: Although incision or resection of the paratenon has been advocated when repairing injured or degenerative tendons, our data suggest that the integrity of the paratenon should be preserved.